Comparative studies on the activities of collagenases from Grimontia hollisae and Clostridium hystoliticum in the hydrolysis of synthetic substrates. (10th February 2018) - Takita, Teisuke; Qian, Jun; Geng, Hongmin; He, Zejian; Nemoto, Sho; Mori, Mariko; Tanaka, Keisuke; Hattori, Shunji; Kojima, Kenji; Yasukawa, Kiyoshi
Abstract: The collagenase produced by a gram-negative bacterium Grimontia hollisae strain 1706B (Ghcol) degrades collagen more efficiently than that produced by a gram-positive bacterium Clostridium histolyticum (Chcol), which is currently the most widely used collagenase in industry [Teramura et al. (Cloning of a novel collagenase gene from the gram-negative bacterium Grimotia ( Vibrio ) hollisae 1706B and its efficient expression in Brevibacillus choshinensis. J Bacteriol 2011;193:3049–3056)]. Here, we compared the Ghcol and Chcol activities using two synthetic substrates. In the hydrolysis of (7-methoxycoumarin-4-yl)acetyl-L-Lys-L-Pro-L-Leu-Gly-L-Leu-[ N 3 -(2, 4-dinitrophenyl)-L-2, 3-diaminopropioyl]-L-Ala-L-Arg-NH2, Ghcol exhibited 350-fold higher activity than Chcol in the absence of CaCl2 and NaCl. The Ghcol activity markedly decreased with increasing concentrations of buffer, CaCl2 or NaCl, while the Chcol activity did not, suggesting that the Ghcol activity was sensitive to solvent components. In the hydrolysis of N -[3-(2-furyl)acryloyl]-L-Leu-Gly-L-Pro-Ala, Ghcol exhibited 16-fold higher activity than Chcol in the absence of CaCl2 and NaCl, and both enzyme activities did not decrease with increasing concentrations of buffer, CaCl2 or NaCl. pH dependences of activity revealed that the ionizable group responsible for acidic p K e may be Glu for Ghcol and Chcol, while that for alkaline p K e may be His for Ghcol and Tyr for Chcol. These striking differences suggest that the catalytic mechanism of Ghcol might be considerably different from that of clostridial collagenases.